Validation of a rotary encoder and power prediction equations during a jump squat - Pustina, Andrew (My University, 2010)
The purpose of this study was twofold: first, it was to determine the validity of a rotary encoder at measuring power and velocity; second, it was to expand the validity of the use of various power prediction equations using counter movement jump height. METHODS: Sixty college students (men n=30; women n=30) performed a jump squat with applied loads of 20%, 40%, and 60% of their body mass. Each jump squat (JS) was simultaneously monitored using a force plate, a rotary encoder, and a contact mat. Peak power (PP) was calculated using the time and position data derived from the rotary encoder, while the force plate determined PP from vertical ground reaction force. The contact mat measured jump height, which was entered into the prediction equations (8, 19) to estimate peak power. All calculations were compared to the force plate. A significant difference was found between force plate measurements and TWA measurements of peak power, average power, peak velocity and average velocity (p<0.01). Pearson correlations showed that rotary encoder power measurements had a strong relationship to force plate power measurements at all loads (r = >0.80). In addition, no significant difference between force plate PP and predicted PP by the Harman equations was found (p = 0.06). The Harman equation had a greater correlation with the force plate in men (r = 0.93 - 0.94) than in women (r = 0.65 - 0.72). The results of this study suggest that the Harman equation should be used to estimate PP of a loaded JS because it was found to be both reliable and valid.
Keywords: Muscle strength -- Testing; Exercise -- Equipment and supplies; Athletes -- Training of